1993
DOI: 10.1108/02651339310051632
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Countertrade Practices with Eastern Europe

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…With this context in mind the comment from one respondent with respect to offset was typical of the reluctants category: "offset demands are only responded to because they are a sine qua non of staying in the competitive running for a deal". It is argued here that this classic follower approach has inherent dangers for the reluctants, excluding them from the potentially huge profits of future business opportunities in the emerging markets of regions such as central and eastern Europe (Kindra et al, 1993). More specifically, offset deals are increasingly being sought for non-military purchases and aerospace companies, among others, need to be conscious of the generally more competitive market conditions prevailing in these sectors.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…With this context in mind the comment from one respondent with respect to offset was typical of the reluctants category: "offset demands are only responded to because they are a sine qua non of staying in the competitive running for a deal". It is argued here that this classic follower approach has inherent dangers for the reluctants, excluding them from the potentially huge profits of future business opportunities in the emerging markets of regions such as central and eastern Europe (Kindra et al, 1993). More specifically, offset deals are increasingly being sought for non-military purchases and aerospace companies, among others, need to be conscious of the generally more competitive market conditions prevailing in these sectors.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, seldom in modern times has the incentive to engage in countertrade been as strong as it is presently, and seldom have the opportunities been so abundant. Incentive has intensified with the necessity to deepen differential advantage in the global recession that has generated worldwide excess capacity and ferocious competition in many markets (Bost and Yeakal, 1992;Kindra et al, 1993;Reisman et al, 1988). More significantly, in the emerging markets of the former COMECON economies, there is vast latent and incipient demand for goods ranging from basic infrastructure items to newly permitted high technology transfer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As such, the complexity of social experience is considered a necessary condition for explaining corrupt practices. Relatedly, the roots of corruption will be conceived in this article as “grounded in a country’s social and cultural history, political and economic development, bureaucratic traditions and policies” (Kindra & Stapenhurst, 1988, p. 1).…”
Section: Approach Of Studymentioning
confidence: 99%
“…Empirical studies (Huszagh and Barksdale, 1986;Kindra et al, 1993;Neale and Shipley 1990) have found that the main benefits firms which derive from CT are market penetration, increased competitiveness and the opportunity to overcome currency and credit problems. Although CT is commonly regarded as "secondbest", to be adopted only when orthodox approaches appear unworkable, a "global countertrade service industry" (Palia, 1990) has arisen to handle CT risks, and many firms operate specialist units to manage CT operations.…”
Section: Countertrading and Foreign Market Entrymentioning
confidence: 99%